European Birds of Conservation Concern: some constructive comments (Avocetta, 2018)
Since 1994 BirdLife International embarked on a very important initiative by producing and updating (in 2004 and 2017) a list of Species of European Conservation Concern (SPECs). Notwithstanding, the present authors noted some flaws in the compilation of data and propose improvement to the methodology followed by BirdLife. In particular, the importance to consider local populations, in most cases described as subspecies; as already highlighted by many researchers, the SPECs methods do not consider them as such. Their conservation is necessary for the potential evolution and acquisition of unique characteristics, which represent important components of biological diversity. The effort to consider subspecies has already been carried out by the 2009/147 EU Directive. Some particular cases are reported and commented upon.
Keywords: SPECs; subspecies conservation; local populations; monitoring